Identifying Multinuclear Organometallic Intermediates in On‐Surface [2+2] Cycloaddition Reactions. Issue 46 (4th October 2019) - Zhang, Ran; Xia, Bowen; Xu, Hu; Lin, Nian
Abstract: We investigate the on‐surface [2+2] cycloaddition reaction of 2, 3, 6, 7, 10, 11‐hexabromotriphenylene (HBTP) on Ag(111), Cu(111), Au(111), and Cu‐dosed Au(111) surfaces using STM and DFT simulation focusing on the organometallic intermediates. The fully debrominated HBTP molecules form an organo‐silver framework on Ag(111) and an organo‐copper framework on Cu(111), both incorporating multinuclear metal adatom clusters. The organo‐silver framework is converted into porous covalent networks via [2+2] cycloaddition above 240 °C. In contrast, the organo‐copper framework is very stable and does not undergo [2+2] cycloaddition even at 300 °C. On Au(111), no organo‐gold intermediate of [2+2] cycloaddition is observed. After loading Cu onto Au(111), the partially debrominated HBTP molecules bind to Cu adatom dimers to form multinuclear organo‐copper complexes at 100 °C which undergo [2+2] cycloaddition at 140 °C. This study shows that the choice of surface can direct the reaction pathway. Abstract : Silver surfer : The [2+2] cycloaddition reaction pathway of 2, 3, 6, 7, 10, 11‐hexabromotriphenylene (HBTP) molecules on a Ag(111) surface results in a porous covalent network via a multinuclear organo‐silver intermediate. In contrast, on a Cu(111) surface no cycloaddition occurs.